Reflection and practice on generative music structuring: the formal problem of ergodicity - e Silva, Gabriel; Mamedes, Clayton (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2019)
This article approaches the subject of musical form from the standpoint of an algorithmic composition practice. It introduces the problem of ergodicity in music, a formal situation at which music development is perceived as static. The concepts of ​General Periodicity by Henri Pousseur and ​Temporal Gestalt by James Tenney gave support to a reflection on the nature of the problem, as well as to formulate a twofold structuring procedure based on ideas of continuity and segmentation of the musical course. The devised method was implemented as a computer program to produce entire pieces of music.